Utilization of Palm Kernel cake for the production of mannanase by an indigenous filamentous fungus, aspergillus niger USM F4 under solid substrate fermentation - Syarifah Ab Rashid; Darah Ibrahim; Ibrahim Che Omar (2011)
A mannanase yielding indigenous fungal culture Aspergillus niger USM F4 which was isolated from decayed palm kernel cake (PKC) collected from a local oil palm processed plant was used in this study. The fungal culture produced high yields of extracellular mannanase under solid-substrate fermentation (SSF) using PKC as a substrate. The results obtained from this study revealed that after five days of cultivation period, a maximum extracellular mannanase activity was 433.84 U/ g substrate and 0.96 mg glucosamine/g substrate of fungal growth. The optimized cultural conditions and medium compositions were 10 g PKC with particle size of 0.5 mm, moisture content of 80% (v/w), inoculums size of 1x107 spores/ml, incubation temperature of 30ºC, static (without mixing), 2% (w/w) of molasses and 4% (w/w) of ammonium nitrate. There was 53.68% increment of mannanase production after optimization compared to before optimization of cultural conditions and medium compositions.